PAPR REDUCTION CONCERNING BER PERFORMANCE IN MIMO-OFDM-BASED NEXT-GEN WIRELESS SYSTEMS- A REVIEW (International Journal of Engineering Sciences & Management Research, 2022)
Today, society's demand for high-speed and reliable wireless communication on mobile devices is paramount. With the rapid proliferation of mobile applications and users, there is a pressing need for a more dependable, high-speed wireless network with increased throughput to address the shortcomings of existing systems in this multiuser environment. In wireless systems, received signals may suffer from corruption due to noise and interferences such as inter-symbol interference and inter-carrier interference when subjected to multipath fading. Moreover, poor bit error rates and high peak-to-average power ratio values can adversely affect signal power and the spectral efficiency of transmitted signals. The integration of orthogonal frequency division multiplexing (OFDM) and multi-input multi-output (MIMO) antenna systems, known as MIMO-OFDM, promises to enhance quality of service and increase throughput to meet the demands of tomorrow. This review article primarily examines various technologies adopted by researchers to improve bit error rates, peak-to-average power ratio, signal-to-noise ratio, and spectral efficiency in wireless systems. We proceed by discussing the limitations and comparing results of conventional methods, schemes, and algorithms proposed by different researchers. Additionally, we focus on MIMO, a multiple-antenna system designed for future multiuser environments, aiming to enhance capacity or achieve high throughput while maintaining good quality of service.